Endogamous Matrilateral Parallel Cousin Marriage: A Maqāṣid al-Sharīʿah Perspective - Baedhowi; Miftachul Jannah; Mahdee Maduerawae (Yayasan Azhar Amanaa Yogyakarta, 2025)
The practice of matrilateral parallel cousin marriage, which refers to marriage between the daughter and the son of two sisters, occurs in Kutoanyar Village, Kedu Sub-district, Temanggung Regency. This practice is noteworthy to analyze because, although it is not categorized as prohibited in Islamic law, it generates various perspectives and assumptions within the community. Particularly concerning potential biological impacts on offspring and the consideration of maqashid shariah values. The purpose of this research is to analyze how this marriage practice is carried out and to analyze it within the framework of maqashid shariah, which includes the five primary objectives of Islamic law: the preservation of religion, lineage, intellect, property, and life. This study employs a qualitative research method with a socio-empirical approach and is classified as field research. The findings indicate that cousin marriages in Kutoanyar Village are commonly arranged by family and are socially accepted by the local community. However, from the perspective of maqashid shariah, such marriages conflict with hifz an-nafs (protection of life), hifz an-nasl (protection of lineage), and hifz al-aql (protection of intellect) due to the emergence of physical and mental disabilities among offspring as a result of these unions. Therefore, while such marriages may be legally permissible in Islam, they should be approached with caution, especially in light of genetic health considerations.